Answer:
Option C is correct.
The expression which is equivalent to (p-q)(x) is, ![x^2 -1 - 5(x-1)](https://tex.z-dn.net/?f=x%5E2%20-1%20-%205%28x-1%29)
Step-by-step explanation:
Given:
and q(x) = 5(x-1)
To find the expression which is equivalent to (p-q)(x):
here p and q both are function assuming;
we can write the expression :
(p-q)(x) = p(x) - q(x) = ![x^2 -1 - 5(x-1)](https://tex.z-dn.net/?f=x%5E2%20-1%20-%205%28x-1%29)
therefore, the expression which is equivalent to (p-q)(x) is; ![x^2 -1 - 5(x-1)](https://tex.z-dn.net/?f=x%5E2%20-1%20-%205%28x-1%29)
= 100 ( 1 + 3/100 ) ^ 25
= 209.377793
= 209.4
I will ask you to turn it in english instead of española.
Answer:
3 and 4 it is 60
is the answer
if you like my answer please like comment and mark me as brilliant
Answer:
4m+5
Step-by-step explanation: